Bacterial Spinal Epidural and Psoas Abscess in Pregnancy Associated with Intravenous Drug Use - Tirtza N. Spiegel Strauss; Sarah L. Pachtman; Burton Rochelson (Case Reports in Obstetrics and Gynecology)
Spontaneous spinal epidural abscess (SEA) is a rare infection of the central nervous system. We report a case of a 25-year-old G3 P0020 at 36 weeks of gestational age with history of intravenous drug abuse presenting with acute-onset and severe back pain. Despite antibiotic therapy, pain worsened and she developed lower extremity weakness. Magnetic resonance imaging (MRI) revealed an SEA, and cesarean delivery was performed secondary to increasing weakness, followed by laminectomy (T9-12) and decompression of epidural abscess. Postoperative course was complicated by a psoas muscle abscess and persistent SEA refractory to antibiotic therapy, requiring surgical reexploration and extended treatment with antibiotics. She was discharged home in stable condition and neonate did well with no resulting sequelae. Spinal epidural and psoas abscesses are rare and diagnosis is often delayed. Prompt recognition and treatment are necessary to prevent catastrophic neurologic consequences, and the diagnosis should be considered in pregnant patients presenting with back pain, especially in those with risk factors.